Coming of age: Towards best practice in women`s artistic gymnastics - Kerr, R.; Barker-Ruchti, N.; Schubring, A.; Cervin, G.; Nunomura, M. (LEaP Research Report, 2015)
This study found a range of six interrelated factors that contributed to gymnasts continuing their elite careers beyond their teenage years, including coaching, body size, finance, love of the sport, continued success and the Code of Points. While all of these factors are significant in their own right, they also connect in a variety of ways to contribute to decisions made by gymnasts to continue their careers into their 20s.